2018
DOI: 10.5194/nhess-18-2717-2018
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction and simulation of an extreme flood event in the Lago Maggiore catchment in 1868

Abstract: Abstract. Heavy precipitation on the south side of the central Alps produced a catastrophic flood in October 1868. We assess the damage and societal impacts, as well as the atmospheric and hydrological drivers using documentary evidence, observations and novel numerical weather and runoff simulations. The greatest damage was concentrated close to the Alpine divide and Lago Maggiore. An atmospheric reanalysis emphasizes the repeated occurrence of streamers of high potential vorticity as precursors of heavy prec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 57 publications
(87 reference statements)
1
23
0
Order By: Relevance
“…The second example used dynamical downscaling, which is also a widely used method. It has been applied for a number of historical weather extremes including blizzards, flash floods, or storms . Fortunato et al .…”
Section: Discussionmentioning
confidence: 99%
“…The second example used dynamical downscaling, which is also a widely used method. It has been applied for a number of historical weather extremes including blizzards, flash floods, or storms . Fortunato et al .…”
Section: Discussionmentioning
confidence: 99%
“…Was flood frequency higher in the mid-19th century? In fact, each series exhibits prominent peaks in the 19th century, e.g., the Rhine in Basel in 1817, 1852, 1876, 1881, and 1882 (see Stucki et al, 2012), Lake Constance in 1817 (see Rössler and Brönnimann, 2018), and Lago Maggiore in 1868 (Stucki et al, 2018). However, we also note a period of low flood frequency in Basel from the 1920s to 1970s, in agreement with a low frequency of peak-over-threshold events in Basel and Ponte Tresa.…”
Section: Flood Frequencymentioning
confidence: 99%
“…While changes in seasonality have been found for European floods (Blöschl et al, 2017), no general increase in flood frequency has so far been detected (Madsen et al, 2014). However, past records suggest that there is considerable decadal variation in flood frequency (e.g., Sturm et al, 2001;Wanner et al, 2004;Glaser et al, 2010). It is reasonable to assume that such variations will continue into the future.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In fact, 20CR has proven to be a valuable input dataset for downscaling heavy-precipitation and windstorm events over the Central Alps back to the 19th century. Stucki et al (2018) showed that downscaling the ensemble 10 mean is not only computationally cheaper, but can be seen as a minimum-error and thus natural approach in well represented areas and distinctive synoptic flow conditions. For an extreme flood in 1868, they found a small smoothing effect of the associated cyclone, which induced southerly moisture flux, i.e.…”
Section: Introductionmentioning
confidence: 99%